Management Of The Qur'an Tahfidz Program In Improving Student Competencies At SMP Plus Darussalam Blokagung Tegalsari Banyuwangi Year 2021-2022 - Mahya aliya; Moh. Dahlan; Subakri Subakri (Cita Konsultindo Research Center, 2023)
The objectives set in this study are: (1) To find out the Management of the Tahfidz Al-Qur'an program in improving student competence at SMP Plus Darussalam Blokagung for the 2021/2022 academic year; (2) to find out how the competence of students at SMP Plus Darussalam Blokagung in the 2021/2022academic year; (3) to find out the supporting and inhibiting factors in the management of tahfidz Al-Qur'an in improving stude nt competence at SMP Plus Darussalam Blokagung for the academic year 2021/2022; This research method uses descriptive qualitative, data collection through interviews, observation and documentation. Data analysis using hubber and miles analysis. The results of the research: In the management of the tahfidz program, the principal plays an important role in running the tahfidz program, and can realize the competence of Islamic students. SMP Plus Darussalam Blokagung is different from other schools where this school has a superior program, namely the tahfidz program, where every day they hold tahfidz al-Qur'an, all students are able to memorize according to the targets set by the school, and student competence after participating in the tahfidz program is getting better. The purpose of writing this thesis is to determine the management of the tahfidz program, competencies, supporting factors, and obstacles to the tahfidz program in improving student competence at SMP Plus Darussalam Blokagung. The form of research used in this thesis is qualitative research using a descriptive approach. The subjects of the research were school principals, student wakasis, and tahfidz teachers. Data collection techniques in this study used interviews, observations, and documentation. The results of this study indicate that first, the management of the tahfidz program in improving student competence at SMP Plus Darussalam Blokagung, overall has gone well, while the implementation includes first, (1) planning; (2) organizing; (3) mobilization; (4) Monitoring the Tahfidz Program. second, competence in terms of memorizing the Qur'an in meeting the targets of the institution. Third, the supporting and inhibiting factors of the tahfidz program, the supporting factors are (1) social environmental factors; (2) the Koran provided by the school for memorizing; (3) the availability of classes and dormitories for tahfidz activities; (4) there is a tahfidz teacher. The inhibiting factors are (1) the lazy nature that arises from students; (2) lack of time for tahfidz activities in terms of memorization; (3) lack of tahfidz teachers.